Osteochondral Allograft Transplantation for Full-Thickness Chondral Defect Utilizing BioUni Technique - Michael P. Campbell MD; John Hayden Sonnier MS; Kevin B. Freedman MD (SAGE Publishing, 2022)
Background: There are several techniques to treat chondral defects. Osteochondral allograft transplantation is an excellent option, and for elongated lesions, there are 2 techniques-the Snowman technique and the BioUni technique. Indications: Osteochondral allograft transplantation is indicated for active individuals with isolated, symptomatic full-thickness chondral defects without concomitant ligamentous injury or malalignment. Technique Description: The lesion on the native condyle is sized. A plug is then harvested from the allograft using a cutting block and sagittal saw. The recipient site is then prepared with an overlapping reamer system with a cutting block. Graft is then implanted in a press-fit manner. Results: Osteochondral allograft transplantation leads to improved patient-reported outcomes. The literature has demonstrated survival rates between 70% and 80% at 10 years. Discussion/Conclusion: Osteochondral allograft transplantation is a restorative cartilage treatment that has good clinical outcomes. The BioUni system is a good option for irregular or elongated lesions.